RÓŻNORODNOŚĆ SPOŁECZNO-KULTUROWA SZWECJI W PODRĘCZNIKACH DO NAUKI JĘZYKA SZWEDZKIEGO - Kowal, Iwona (Neofilolog, 2018)
The paper discusses specific features of the Swedish sociocultural reality and the way the sociocultural diversity of the country is presented in language textbooks for Swedish language learners. The analysis is longitudinal in nature i.e. it concerns two editions of textbooks published in Sweden between 1996 and 2014. The presentation of Swedish sociocultural diversity is both explicit and implicit in nature, with changes in ethnic diversity, household diversity, and family diversity being the most dynamic ones. However, a number of differences between both textbooks are noticeable: in the older version information is presented mainly in an explicit form while its newer counterpart demonstrates the diversity of Swedish society both explicitly and implicitly.